Dealing With Discrimination: Women Labor and Oil Palm Plantation Expansion in Indonesia - Lengga Pradipta (Journal of Indonesian Social Sciences and Humanities, 2017)
Oil palm plantations have expanded massively in the isolated areas of Indonesia in the last decades. They cover more than 13.5 million hectares across Indonesia and spread into more than 10 provinces. Riau and West Sumatra are the two provinces that have been targeted for oil palm plantation expansion. When oil palm companies entered Riau and West Sumatra, they started to expand their operations and promised to provide the employment for local people, especially women. At first, thiswent smoothly. However, along with many other social, economic and environmental issues, oil palm companies are no longer giving adequate protection for the women in the labor force. Women operate in unsafe working conditions and always get an unfair share of income. The health of women who work for oil palm companies suffers greatly. They have to handle pesticides and fertilizers without protection such as masks and gloves. Although women put much effort in working for the oil palm companies, they always get lower financial compensation than the men. This situation demonstratesthe tremendous discrimination in the oil palm industry. This is violates many regulations, especially the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) article 11, which mentions that all parties shall take all appropriate measures to eliminate discrimination against women in the field of employment to protect health and safety in the workplace and to ensure equal wages between men and women. This situation not only contravenes CEDAW, but also Act Number 13/2003 about Manpower (article22) which is concerned with the safe working environment and equal wages among employees. The aim of this study is to investigate the current situation in the oil palm industry in Indonesia and how companies discriminate against women without considering the international and national regulations. This study is not only focuses on the oil palm industry itself, but also on women, and how they survive as employees of oil palm companies. This study used qualitative methods, which have been conducted through observation, key informant interviews and secondary data. The study also reveals that in order to solve the case about women labor in oil palm plantations, critical changes are urgently needed, not only from government as the policy makers, but also from many other stakeholders.